The Role of AI in the Legislative Documents of the European Union Countries - qizi , Yuldasheva Yulduz Xamza (Miasto Przyszłości, 2024)
The article shows an analysis of different strategic approaches in documents concerning artificial intelligence (AI), actions initiated by the European countries, and legislations enacted by the European Commission. It highlights the diverse directions taken in these initiatives. Furthermore, it delves into the recently implemented "AI Act" by the European Commission in March 2024, offering a comparative examination of the EU’s AI policy in relation to that of other nations like the United States and China.